PELATIHAN PEMBUATAN DAN PEMASARAN OLAHAN JERUK SORTIR MENJADI DODOL, MANISAN DAN TEH DI DESA KARANG JAYA KECAMATAN SELUPU REJANG - Ria Dwi Jayati; Nur Fitriyana; Lucy Asri Purwasi; Linna Fitriani (LP4MK STKIP PGRI Lubuklinggau, 2023)
This community service (PKM) aims to provide training to local residents in the manufacture and marketing of processed sorting oranges into dodol, sweets, and tea. Sortir oranges are a type of orange that has good quality and the price is relatively cheaper than ordinary oranges. Therefore, the processing of sorted oranges into value-added processed products such as dodol, sweets and tea can increase the economic value for local residents. This service was carried out in Karang Jaya Village, Selupu Rejang District. After being implemented, this PKM succeeded in providing benefits to the surrounding community. The procedures that have been carried out use the method of observation, socialization, training and continued with direct practice. Local residents who have participated in the training have succeeded in producing quality sorted orange processed products and successfully marketing them effectively. This can be seen from the increase in the income of local residents and the increase in consumer buying interest in processed orange sorting products. The outputs of the activity are (1) the partners' knowledge, skills and income increase, (2) produce sorted orange processed products in the form of dodol, sweets and tea. Thus, training in the manufacture and marketing of processed sorted oranges into dodol, sweets and tea has a positive impact on increasing the income, knowledge and skills of the local community. This is expected to provide long-term benefits for the community and strengthen the local economy.